KEPEMILIKAN RUMAH ORANG ASING YANG TINGGAL DI INDONESIA - Suryadi, Suryadi; Nugroho, Diko Setiawan (UNES Law Review, 2023)
The title of this article is "Foreign Home Ownership in Indonesia". The purpose of this study is to analyze the regulation of house ownership for foreigners living in Indonesia and the procedures for foreigners to own houses in Indonesia. The need for housing as a dwelling or place of refuge is a basic need of every human being, as is the need for food, clothing and shelter. Anyone who lives in a house is possessive and lives in their own house. Some people occupy other people's homes, whether they rent them out or not. One of the parties who can own a house as a residence is a foreigner residing in Indonesia. Foreign housing is based on certain property rights. This type of research uses legal research with a focus on normative research. In summary, the regulations regarding home ownership for foreigners residing in Indonesia are: According to Government Decree No. 41 of 1996 on Requirements for Foreigners to Own Houses and Minister of Agriculture/Head of Land Authority Decree No. 7 of 1996, both regulations require foreign owned houses to meet the following conditions: It isRequired. In Indonesia, housing refers to a house built on land. Owned or leased shares in buildings.